2010
DOI: 10.1186/1471-2156-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage scan for factors of metabolic syndrome in a Chinese population

Abstract: BackgroundShared genetic factors may contribute to the phenotypic clustering of different components of the metabolic syndrome (MES). This study aims to identify genetic loci that contribute to individual or multiple factors related to MES.ResultsWe studied 478 normoglycemic subjects ascertained through 163 families participating in the Hong Kong Family Diabetes Study. Factor analysis on 15 MES-related traits yielded 6 factors including adiposity factor (body mass index, waist and hip circumferences), insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
0
17
0
3
Order By: Relevance
“…The association between the CAV1 variant and dyslipidemia is supported by genome-wide studies showing association of CAV1 gene proximal regions to low HDL and high triglycerides in two ethnically different cohorts [26, 35, 36]. Additionally, CAV1 KO mice display alterations in lipid composition (triglycerides, LDL and HDL), lending further support to a role for CAV1 in the complex regulation of lipoprotein metabolism and cholesterol efflux [8].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The association between the CAV1 variant and dyslipidemia is supported by genome-wide studies showing association of CAV1 gene proximal regions to low HDL and high triglycerides in two ethnically different cohorts [26, 35, 36]. Additionally, CAV1 KO mice display alterations in lipid composition (triglycerides, LDL and HDL), lending further support to a role for CAV1 in the complex regulation of lipoprotein metabolism and cholesterol efflux [8].…”
Section: Discussionmentioning
confidence: 96%
“…To date, information concerning the CAV1 gene and MetS is scarce, and is mainly based on animal studies [10, 25]. Of note, a particular region in chromosome 7 close to the CAV1 gene has been linked to both glucose and lipid factors but not increased adiposity in Asians, being the most associated region to both metabolic traits [26]. Also, linkage analysis showed that a region close to 7q.31 where CAV1 is located was related to metabolic syndrome [27].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide linkage studies in multiple populations found evidence for linkage of MetS on chromosome 1, 2, 3q37, 7q, 16 [17][21]. Principal component factor analysis was also used to define quantitative phenotypes to identify the underlying genetic basis of MetS [22][30]. Although a number of quantitative trait loci (QTLs) were successfully identified, no specific gene or mutation has been found as a result of these linkage studies.…”
Section: Introductionmentioning
confidence: 99%
“…Ventricular arrhythmia in German Shepherds is a complex phenotype which is likely to be influenced by many loci of small effects, so our power to detect any given locus is likely to be low, particularly with widely‐spaced microsatellite markers. Given this fact, it is valuable to identify markers under “suggestive linkage” with the trait (for e.g., [Tam et al, 2010]) as a starting point for future multilocus investigations. We considered all loci with LOD scores greater than 1.0 as demonstrating suggestive linkage.…”
Section: Methodsmentioning
confidence: 99%